THE COMPOUNDABILITY OF PHRASES? THE PHRASABILITY OF COMPOUNDS?--PREDICTIONS FOR ENGLISH/ES. - Ekanamaya, Tanya N. I. (Sri Lanka Journal of the Humanities, 2007)
The article discusses how the linking of words into compounds and phrases cannot account for some linguistic forms. The author comments on how the classification of linguistic constructions is determined by syntax and context. He notes how Standard Sri Lankan English (SSLE) doesn't use word stress to identify phrases from compounds.